2006
DOI: 10.1111/j.1467-8624.2006.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Do the Effects of Early Severe Deprivation on Cognition Persist Into Early Adolescence? Findings From the English and Romanian Adoptees Study

Abstract: Cognitive outcomes at age 11 of 131 Romanian adoptees from institutions were compared with 50 U.K. adopted children. Key findings were of both continuity and change: (1) marked adverse effects persisted at age 11 for many of the children who were over 6 months on arrival; (2) there was some catch-up between ages 6 and 11 for the bottom 15%; (3) there was a decrease of 15 points for those over 6 months on arrival, but no differentiation within the 6-42-month range; (4) there was marked heterogeneity of outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
274
1
18

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(304 citation statements)
references
References 67 publications
9
274
1
18
Order By: Relevance
“…These reductions in performance were significant above and beyond the effects of early deprivation on global IQ, which have been noted in this study and previously reported in similar samples (40,41). Although several studies have documented reduced EF performance in PI children (11)(12)(13)(14)(15), this is the youngest age (2.5-4 y old) and the soonest postadoption timing (1 y after adoption) to document lower EF performance using observational laboratory data.…”
Section: Discussionmentioning
confidence: 58%
“…These reductions in performance were significant above and beyond the effects of early deprivation on global IQ, which have been noted in this study and previously reported in similar samples (40,41). Although several studies have documented reduced EF performance in PI children (11)(12)(13)(14)(15), this is the youngest age (2.5-4 y old) and the soonest postadoption timing (1 y after adoption) to document lower EF performance using observational laboratory data.…”
Section: Discussionmentioning
confidence: 58%
“…The lack of a stable caregiver is a stressor in human infant development (49), with institutionalized children showing increased anxiety and disrupted socio-emotional functioning (27)(28)(29)(30)(49)(50)(51). In nonhuman primates, social deprivation studies have similarly demonstrated the role of species-typical maternal care in the development of cognitive and socio-emotional functioning (31)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Socially deprived children demonstrate poor emotional and social competence, including lower sympathetic concern, increased risk for psychiatric disorders, and enlarged amygdala volumes, indicative of high anxiety (27)(28)(29)(30). Although adoptive care can mitigate these negative effects, orphaned children typically show lasting socio-emotional disruptions (30).…”
mentioning
confidence: 99%
“…Percebe-se que esse resultado possivelmente reflete o fato de que hoje há uma maior difusão de informações acerca do desenvolvimento infantil e do valor do convívio com a família, no processo de socialização primária da criança e formação do apego. Esse acesso à informação pode ocorrer não apenas em atividades de capacitação profissional, mas inclusive por meio da mídia e outros meios que procuram demonstrar o quanto pode ser nociva a separação ou a perda para a criança da figura dos pais e demais familiares, mesmo quando o distanciamento é temporário 17,18 .…”
Section: Percepções Das Educadoras Acerca Da Criança Em Acolhimento Iunclassified
“…Embora a sua existência seja reconhecida por especialistas 9,17,18 , o estresse gerado pela imperiosa necessidade de se adequar à realidade apresentada pelo abrigo provém justamente do fato de que a criança institucionalizada acaba por ter que lidar com situações que se revestem de estranhamento e despertam sentimentos de insegurança difíceis de serem aplacados. A criança institucionalizada experimenta, assim, a chamada separação total (noite e dia), sendo muitas vezes levada até a instituição sem qualquer preparo anterior.…”
Section: Percepções Das Educadoras Acerca Da Criança Em Acolhimento Iunclassified